2020
DOI: 10.2346/tire.20.190207
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Comparison of Speed-Dependent Rolling Coefficients in Small Cycling Tires

Abstract: In this article, the methodology and results of an experimental campaign on small and slick bicycle tires are presented. The test was developed to compare the rolling resistance of tires to be used in high-speed competitions for streamlined human-powered vehicles. After an explanation of the theoretical background for the measurement, the test-rig and the adopted procedure to measure and subtract aerodynamic effects are presented. The obtained data show that the rolling resistance coefficient has a nonlinear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition, the tube type and speed dependency of rolling resistance has been known for many years. Baldissera et al [ 6 ] confirmed this increase in rolling resistance coefficient with increasing speed in their experiments. Nonetheless, this increase has minimal relevance for utility cyclists since these changes occur at velocities much higher than are typical for utility cyclists.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…In addition, the tube type and speed dependency of rolling resistance has been known for many years. Baldissera et al [ 6 ] confirmed this increase in rolling resistance coefficient with increasing speed in their experiments. Nonetheless, this increase has minimal relevance for utility cyclists since these changes occur at velocities much higher than are typical for utility cyclists.…”
Section: Introductionmentioning
confidence: 58%
“…Depending on the application, riders attempt to reduce some of these driving resistances in order to reduce driving effort. For example, rolling resistance and aerodynamic forces are reduced in competitive cycling to maintain high acceleration and high speeds on a given track, including ascending slopes [ 6 ]. In contrast, utility cyclists try to avoid hills to reduce the cycling effort required [ 7 ] and are willing to pedal a longer distance instead.…”
Section: Introductionmentioning
confidence: 99%
“…Baldissera [9] performed coast-down tests with a full fairing recumbent bike to evaluate the linear dependent and the inverse linear on vehicle speed dependent rolling resistance coefficients. Last year Baldissera published the results of experiments on a drum [10] again with focus on high speed.…”
Section: Rolling Resistancementioning
confidence: 99%